Exploring student learning obstacles in solving mathematical reasoning problems on squares and rectangles - Rahma Adinda Sartika; Dadan Dasari (Universitas Muhammadiyah Malang, 2025)
Mathematical reasoning ability is an essential foundation that every student must master. However, the reality in the field shows that many students still struggle when dealing with reasoning problems, even on basic geometry topics such as squares and rectangles. Therefore, this study aims to deeply analyze the learning obstacles experienced by students when solving reasoning problems related to squares and rectangles. This research uses a qualitative descriptive method that allows for an in-depth exploration of the phenomena being studied. The instruments used are specially designed problems concerning squares and rectangles, aimed at measuring indicators of students’ mathematical reasoning abilities. Data were collected through student ability tests, interviews, and supporting documentation. The subjects of the study consisted of 32 junior high school students in Bandung City. The data analysis revealed that students experienced several learning obstacles, namely an inability to apply the correct concepts or formulas, indicating weak conceptual understanding, as well as frequent errors in mathematical notation or symbols and in mathematical operations. Based on these findings, the study concludes that students face three main types of learning obstacles: instrumental ontogenic obstacles, conceptual ontogenic obstacles, and epistemological obstacles.